2021
DOI: 10.3390/biom11101492
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CNOT2 Induces Apoptosis via MID1IP1 in Colorectal Cancer Cells by Activating p53

Abstract: CCR4-NOT transcription complex subunit 2 (CNOT2), a subunit of the CCR4-NOT complex, has been described in cancer progression. The CNOT complex plays an important role in multiple cellular functions. Recent studies in our laboratory showed that CNOT2 promotes breast cancer cell proliferation and angiogenesis. In addition, CNOT2 signals are critically related to apoptosis induced by atorvastatin in lung cancer cells. Furthermore, depletion of CNOT2 was shown to enhance the antitumor effect of midline 1 interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…In addition, c-Myc is involved in cell proliferation, cell cycle, metabolism, and survival in cancer cells [ 29 ]. Previously, we showed that the inhibition of CCR4-NOT transcription complex subunit 2 (CNOT2) induces apoptosis through MID1IP1 by activating p53 [ 17 ]. Furthermore, previous studies have shown that MID1IP1 regulates cancer cell growth through c-Myc regulation [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, c-Myc is involved in cell proliferation, cell cycle, metabolism, and survival in cancer cells [ 29 ]. Previously, we showed that the inhibition of CCR4-NOT transcription complex subunit 2 (CNOT2) induces apoptosis through MID1IP1 by activating p53 [ 17 ]. Furthermore, previous studies have shown that MID1IP1 regulates cancer cell growth through c-Myc regulation [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [ 17 ] showed that knockdown of CNOT2 induces apoptosis with MID1IP1 in colon cancer cells via p53 activation. Furthermore, MID1IP1 regulates liver cancer growth through c-Myc mediated by CNOT2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations